Description of a new species of Pleciobates Esaki, 1930 (Hemiptera: Heteroptera: Gerridae) from Hainan Island, China - Leng, Zhaoqi; Ye, Zhen (Zootaxa, 2023)
This paper provides the description of a new species, Pleciobates herczeki sp. nov., from Hainan Island, China. Photographs of the male and female habitus are provided, accompanied by line drawings of female structures, male genitalic structures, in situ habitus and a distributional map for the newly described species.